Oral health condition and practices as indicators of need for oral health promotion among elderly individuals in two rural communities in Ibarapa, Nigeria (2020)
Targeting oral health promotion among elderly individuals in rural settings requires baseline information on their oral health condition and practices as oral conditions are highly influenced by behavioral factors, which are culturally related in such settings. To determine the association between oral health condition and practices of elders in two rural communities in southwestern Nigeria. A total of 357 residents aged 60 years or older participated in this cross-sectional survey conducted in randomly selected clusters in Igboora and Idere in Ibarapa, Southwest Nigeria. Information on sociodemographic characteristics, oral health practices (tooth cleaning material, frequency of tooth cleaning, utilization of dental services) and oral hygiene status was obtained using interviewer-administered questionnaire. Information on oral conditions such as dental caries experience, tooth mobility and number of teeth present were obtained by conducting oral examination. Data obtained were analyzed with the Statistical Package for Social Sciences (SPSS). Of 357 participants, 183 (51.3%) had missing tooth/teeth, 157 (44.0%) had mobile tooth/ teeth, 114 (31.9%) had decayed tooth/teeth and 343 (96.1%) had poor oral hygiene. About a third 122 (34.2%) of the participants had consulted a dentist previously, out of whom 120 (98.4%) reported that pain was the main reason for doing so. The main reason for not visiting the dentist was: “no problem with me as tooth problems and its eventual loss occur with ageing” 178 (75.7%). Less frequent tooth cleaning and poor oral hygiene were associated with presence of mobile tooth/teeth and incomplete dentition (p<0.05). Presence of mobile (OR=1.80, 95%CI:1.09,2.98, p=0.023), decayed (OR=1.81, 95%CI:1.09,3.00, p=0.022) or missing teeth (OR=5.24, 95%CI:3.05,8.98, p<0.001) were predictors of previous dental consultation. Poor oral hygiene was highly prevalent among elders in the rural communities. Less frequent tooth cleaning and poor oral hygiene were associated with presence of mobile tooth/teeth and incomplete dentition. Presence of mobile teeth, decayed teeth and missing teeth were significant predictors of previous dental consultation.